STUDI ANATOMI DAUN JENIS-JENIS AVERRHOA DI INDONESIA UNTUK MEMPERTEGAS STATUS TAKSONOMINYA - Sunarti, Siti; Rugayah, Rugayah; Tihurua, Eka Fatmawati (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Leaves anatomy of Averrhoa spp. in Indonesia have been studied for supporting morphological character which used to recognize four species: A. carambola, A. bilimbi, A. leucopetala and A. dolichocarpa. The letter two species have leave crowded terminally or near the top of stem similar to those leave of A. bilimbi, whereas the fruit shape similar to A. carambola.The result of this study indicated that, these four species showed differently in their thickness of lamina and epidermis cell as well.